Comparison of codon usage bias across leishmania and trypanosomatids to understand mRNA secondary structure, relative protein abundance and pathway functions - Subramanian, Abhishek; Sarkar, Ram Rup (Genomics, 2015)
Understanding the variations in gene organization and its effect on the phenotype across different Leishmania species, and to study differential clinical manifestations of parasite within the host, we performed large scale analysis of codon usage patterns between Leishmania and other known Trypanosomatid species. We present; the causes and consequences of codon usage bias in Leishmania genomes with respect to mutational pressure, translational selection and amino acid composition bias. We establish GC bias at wobble position that governs codon usage bias across Leishmania species, rather than amino acid composition bias. We found that, within Leishmania, homogenous codon context coding for less frequent amino acid pairs and codons avoiding formation of folding structures in mRNA are essentially chosen. We predicted putative differences in global expression between genes belonging to specific pathways across Leishmania. This explains the role of evolution in shaping the otherwise conserved genome to demonstrate species-specific function-level differences for efficient survival. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Amino acid bias; Base composition; Codon usage bias; Leishmania; Mutation; Selection bias; Species specificity